Tax evasion and tax avoidance in the towns of the Kingdom of Naples (XV-XVIII centuries) - Bulgarelli Lukacs, Alessandra (Universidad de Málaga. Facultad de Filosofía y Letras, 2016)
The phenomenon of tax fraud was rooted in the tax system of the old regime. The main reasons were: the magnitude of the number of the privileged, the negotiatory nature of fiscal relations between the Sovereign and his subjects, the decentralised management of taxation where a leading role was played in this by the intermediary bodies throughout the territory. Another factor was the autonomy enjoyed at local level, which was also a source of particularism, heterogeneity and excessive power on the part of the urban élite (Fortea Pérez). Many of these characteristics, relating specifically to sixteenth and seventeenth-century Castile, were also common to other areas of Europe as a result of jurisdictional fragmentation (Epstein, Dincecco). In order to describe the peculiar physiognomy of the Kingdom in the field of tax evasion, I shall try to answer questions on whether and how this phenomenon followed the above-mentioned centuries-old patterns

El fenómeno del fraude fiscal es inherente al sistema tributario del antiguo régimen. Las principales razones fueron: la gran cantidad de privilegiados implicados en el sistema; la naturaleza per se negociadora de las relaciones fiscales entre el soberano y sus súbditos; la gestión descentralizada de los impuestos y el papel substancial que jugaron en todo ello los organismos intermedios. Otro factor fue la autonomía de que gozaron en el ámbito local, lo que era también una fuente de particularismos, así como la heterogeneidad y el poder excesivo por parte de la élite urbana (Fortea Pérez). Muchas de estas características, específicamente relacionado con la Castilla de los siglos XVI y XVII, también eran comunes a otras zonas de Europa como resultado de la fragmentación jurisdiccional (Epstein, Dincecco). Para describir la fisonomía peculiar del Reino en el campo de la evasión fiscal, voy a tratar de responder a las preguntas sobre cómo este fenómeno siguió los viejos patrones de los mencionados siglos
Keywords: Fraude fiscal - Historia - S. XV-XVIII; Catastro; Élites urbanas; Relaciones entre el gobierno y las comunidades locales; Privilegiados y no privilegiados; Catastre; Urban élites; Relationship between government and local communities; Privileged and not privileged